A gradient-modified carbon fiber reinforced ceramic matrix composite and a method for preparing the same

CN122916698APending Publication Date: 2026-10-16AEROSPACE INST OF ADVANCED MATERIALS & PROCESSING TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202611271819.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-20
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

本发明通过变密度针刺工艺构建具有梯度孔隙结构的碳纤维预制体,经化学气相渗透沉积热解碳界面层后,结合浸渍-固化-裂解工艺与分区分阶段升温定向反应熔渗实现了预制体结构和陶瓷组元的双重梯度改性,解决了现有技术中陶瓷组元分布单一、梯度结构局限及超高温抗烧蚀性能与力学性能难以兼顾的问题

Benefits of technology

(1)现有技术CN115385712A虽然公开了一种高熵超高温陶瓷基复合材料及其制备方法,但其高熵陶瓷均匀分布会导致结构增重及性能浪费等问题,而本发明创新性地设计了梯度结构,使高熵陶瓷富集于外层(例如占总厚度30~40%),内层保持为SiC基体(占总厚度10~30%),如此可以在保证材料耐2300℃超高温抗烧蚀性能的同时减轻了结构重量,密度梯度范围可以控制在2.0~2.82g/cm3范围,较现有均匀分布方案进一步减重,实现了超高温防护与结构轻量化的协同优化。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916698A_ABST
    Figure CN122916698A_ABST
Patent Text Reader

Abstract

The present application relates to a kind of gradient modified carbon fiber reinforced ceramic matrix composite and its preparation method.The composite includes outer layer, middle layer and inner layer in turn along the thickness direction;The outer layer matrix phase is (Zr, Hf, Ta, Nb, Ti) C x -SiC;The middle layer matrix phase is ZrC-SiC;The inner layer matrix phase is SiC;The method is: after preparing carbon fiber preform with gradient pore structure and depositing pyrolytic carbon interface layer, by impregnation-curing-pyrolysis, high-entropy ceramic precursor is pre-distributed along the thickness direction in gradient, finally, by three-temperature-zone isolation tool, it is carried out to realize the gradient distribution of preform structure and ceramic component by staged heating reaction infiltration.The present application solves the problems of single distribution of high-entropy ceramics, gradient structure limitation and difficulty in considering superhigh-temperature ablation resistance and mechanical properties, and the prepared material has excellent high-temperature oxidation resistance and excellent high-temperature mechanical properties above 2300 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of ultra-high temperature ceramic matrix composite material preparation technology, and particularly relates to a gradient modified carbon fiber reinforced ceramic matrix composite material and its preparation method. Background Technology

[0002] Carbon fiber reinforced ultra-high temperature ceramic matrix composites (C f UHTCs (Ultra-High Temperature Coefficients) have significant application prospects in extreme environment components of high-speed aircraft due to their high melting point, high specific strength, and excellent ablation resistance. As service environments become increasingly harsh, the surface temperature of thermal protection components has exceeded 2000℃, and existing single-homogeneous ceramic matrix composites are unable to simultaneously meet the dual performance requirements of ultra-high temperature ablation resistance and structural load-bearing capacity.

[0003] For applications requiring ultra-high temperature ablation resistance, high-entropy ceramics, due to their superior high-temperature stability resulting from the "high-entropy effect," have become important modifying components. Chinese patent application CN115385712A discloses a high-entropy ultra-high temperature ceramic matrix composite material and its preparation method. This method involves introducing high-entropy carbide ceramics into a carbon fiber preform to obtain C... f / (Ti a Zr b Hf c Nb d Ta e The patent application proposes a C-SiC high-entropy ultra-high temperature ceramic matrix composite. However, in this case, the high-entropy carbides are still relatively uniformly distributed in the composite material, failing to fully utilize the performance advantages of high-entropy ceramics under extreme ablation environments. Furthermore, the uniform distribution of high-entropy ceramics increases the overall material density, which is detrimental to weight reduction in aircraft structures. In addition, the formation of high-entropy carbide solid solutions often requires temperatures above 1900℃, making it difficult to efficiently bond high-entropy carbides with continuous fibers and avoid fiber damage.

[0004] To further optimize structural performance, gradient design has become an important development direction for ceramic matrix composites. Chinese patent CN110627517B discloses a gradient ultra-high temperature ceramic matrix composite material and its preparation method. This method involves compounding a zirconium carbide slurry with carbon cloth at gradient concentrations, and layering multiple prepregs to achieve a gradient change in powder content along the thickness direction. However, this technology lacks gradient design of ceramic components. Under ultra-high temperature service conditions, a severe temperature gradient exists along the material's thickness direction. This design cannot solve the problem of interfacial stress concentration caused by the mismatch of thermal expansion coefficients, easily leading to cracks within the material and subsequent ablation layer spalling failure. Furthermore, this patent does not involve the introduction of high-entropy ceramics, resulting in limited improvement in ablation resistance in ultra-high temperature environments above 2300℃.

[0005] In terms of preparation technology, reactive infiltration has become the mainstream preparation technology for ceramic matrix composites due to its high efficiency and good density. Chinese patent CN108585906B discloses a C... f A method for preparing ZrC-SiC ultra-high temperature ceramic matrix composites involves multiple vacuum impregnation-curing-pyrolysis-carbothermic reduction processes to obtain nanoporous C. f The ZrC-C preform is then infiltrated with molten silicon or molten silicon-zirconium alloy via reactive infiltration. However, this patented technology has the following limitations: the carbon fibers inside the preform lack interfacial protection, making the reactive infiltration process prone to fiber damage; traditional reactive infiltration struggles to achieve controllable introduction and gradient distribution of high-entropy ceramics, and high-entropy components are prone to segregation or incomplete reaction during the infiltration process; conventional infiltration typically forms a homogeneous matrix, which cannot simultaneously meet the dual requirements of ultra-high temperature ablation resistance on the surface and high internal mechanical properties. When the material surface is subjected to extreme heat flows above 2300℃, the homogeneous matrix may fail rapidly due to insufficient surface ablation-resistant components, or experience brittle fracture due to excessively high overall modulus.

[0006] Therefore, there is an urgent need to develop a novel ceramic matrix composite material based on the dual gradient modification of structure and components of high-entropy ceramics and its preparation method. Through the gradient design of preform structure and ceramic components, the ultra-high temperature ablation resistance and high temperature mechanical properties can be synergistically improved to meet the service requirements in extreme environments above 2300℃. Summary of the Invention

[0007] To address one or more technical problems existing in the prior art, this invention provides a gradient-modified carbon fiber reinforced ceramic matrix composite material and its preparation method. This invention constructs a carbon fiber preform with a gradient porosity structure through a variable-density needle punching process. After chemical vapor infiltration deposition of a pyrolytic carbon interface layer, a dual gradient modification of the preform structure and ceramic components is achieved by combining an impregnation-curing-pyrolysis process with zoned, staged, temperature-increasing, directional reactive melting infiltration. This solves the problems of single ceramic component distribution, limited gradient structure, and difficulty in simultaneously achieving high-temperature ablation resistance and mechanical properties in the prior art.

[0008] In a first aspect, the present invention provides a gradient-modified carbon fiber reinforced ceramic matrix composite material, wherein the carbon fiber reinforced ceramic matrix composite material comprises, sequentially from the near-ablation end to the far-ablation end along the thickness direction, an outer layer, a middle layer, and an inner layer; the outer layer is a near-ablation surface layer, and the outer layer matrix phase comprises (Zr, Hf, Ta, Nb, Ti)C x The high-entropy carbide solid solution and the SiC accompanying phase generated in situ during the preparation process; the middle matrix phase is ZrC-SiC; the inner layer is a far-ablation surface layer, and the inner matrix phase is SiC; the reinforcement of the carbon fiber reinforced ceramic matrix composite material is a carbon fiber preform with a gradient pore structure along the thickness direction.

[0009] Preferably, the thickness of the outer layer accounts for 30-40% of the total thickness of the carbon fiber reinforced ceramic matrix composite material; the thickness of the middle layer accounts for 40-50% of the total thickness of the carbon fiber reinforced ceramic matrix composite material; and the thickness of the inner layer accounts for 10-30% of the total thickness of the carbon fiber reinforced ceramic matrix composite material.

[0010] In a second aspect, the present invention provides a method for preparing gradient-modified carbon fiber reinforced ceramic matrix composites, the method comprising the following steps: (1) A carbon fiber preform with a gradient pore structure was prepared by a variable density needle punching process; (2) A pyrolytic carbon interface layer is deposited on the carbon fiber surface of the carbon fiber preform with a gradient pore structure to obtain a low-density C / C porous preform; (3) Prepare a nanocomposite sol containing five kinds of high-entropy carbide ceramic particles and thermosetting phenolic resin, and use the nanocomposite sol as an impregnation liquid to perform an impregnation-curing-pyrolysis process on the low-density C / C porous preform, so that the high-entropy ceramic precursor is pre-distributed in a gradient along the thickness direction to obtain the first composite material; the high-entropy ceramic precursor is a composite of high-entropy carbide ceramic particles and pyrolyzed carbon; (4) The first composite material is placed in a three-temperature zone isolation fixture and subjected to zoned and staged heating reaction melting infiltration to obtain a second composite material including an inner matrix phase, a middle matrix phase and an outer matrix phase; (5) The second composite material is kept at 1600~1800℃ under inert gas protection to obtain a gradient modified carbon fiber reinforced ceramic matrix composite material.

[0011] Preferably, in step (1): the carbon fiber preform has a gradient porosity structure along its thickness direction; when the carbon fiber preform is prepared using a variable density needle punching process, the needle punching density of the preform region used to form the outer layer of the carbon fiber reinforced ceramic matrix composite is 45~55 needles / cm. 2 The interlayer density is 0.6~0.8 g / cm³. 3 The porosity is 50-60%, and the needle density of the preform region used to form the middle layer of the carbon fiber reinforced ceramic matrix composite is 25-35 needles / cm. 2 The interlayer density is 0.9~1.1 g / cm³. 3 The porosity is 30-40%, and the needle density of the preform region used to form the inner layer of the carbon fiber reinforced ceramic matrix composite is 15-25 needles / cm. 2 The interlayer density is 1.2~1.4 g / cm³. 3 The porosity is 15-25%.

[0012] Preferably, in step (2): the pyrolytic carbon interface layer is deposited by chemical vapor infiltration; the thickness of the pyrolytic carbon interface layer is 200~500 nm; and / or the density of the low-density C / C porous preform is 1.10~1.40 g / cm³. 3 .

[0013] Preferably, in step (3): the nanocomposite sol is uniformly mixed from high-entropy carbide ceramic particles, thermosetting phenolic resin, hexamethylenetetramine, dispersant, and solvent; the high-entropy carbide ceramic particles are composed of ZrC nanoparticles, HfC nanoparticles, TaC nanoparticles, NbC nanoparticles, and TiC nanoparticles in a molar ratio of 1:1:1:1:1; the dispersant is polyvinyl butyral and / or a silane coupling agent; the solvent is anhydrous ethanol and / or acetone; preferably, the particle size of ZrC nanoparticles, HfC nanoparticles, TaC nanoparticles, NbC nanoparticles, and / or TiC nanoparticles is 50~200 nm; preferably, the residual carbon rate of the thermosetting phenolic resin is 40~50%; preferably, the solvent is composed of anhydrous ethanol and acetone in a volume ratio of 1:( The mixture consists of 0.5~1.5% high-entropy carbide ceramic particles and thermosetting phenolic resin. Preferably, the mass ratio of the high-entropy carbide ceramic particles to the thermosetting phenolic resin is (3~5):1, the mass ratio of the thermosetting phenolic resin to hexamethylenetetramine is (10~15):1, and the mass ratio of the high-entropy carbide ceramic particles to the dispersant is (20~30):1. Preferably, the solid content of the nanocomposite sol is 30~40wt%. And / or the number of cycles of the impregnation-curing-pyrolysis process is 2~4 times. In each impregnation-curing-pyrolysis process, the impregnation is vacuum impregnation, carried out under an absolute pressure ≤100Pa, the impregnation time is 30~60min, the curing is curing at 80~120℃ for 2~4h, and the pyrolysis is pyrolysis at 900~1000℃ for 1~3h.

[0014] Preferably, in step (4): the inner cavity of the three-temperature zone isolation fixture includes, along the thickness direction, a high-temperature zone for filling high-entropy silicide alloy powder, a medium-temperature zone for filling ZrSi2 and Si mixed powder, and a low-temperature zone for filling silicon powder, wherein the high-temperature zone, the medium-temperature zone, and the low-temperature zone are isolated from each other; the high-entropy silicide alloy powder filled in the high-temperature zone is used to form the outer matrix phase of the carbon fiber reinforced ceramic matrix composite material after reaction melting and infiltration, and the ZrSi2 and Si mixed powder filled in the medium-temperature zone is used to form the middle matrix phase of the carbon fiber reinforced ceramic matrix composite material after reaction melting and infiltration. The silicon powder filled in the low-temperature zone is used to form the inner matrix phase of the carbon fiber reinforced ceramic matrix composite material after reactive melting and infiltration; the high-entropy silicide alloy powder is composed of ZrSi2 powder, HfSi2 powder, TaSi2 powder, NbSi2 powder and TiSi2 powder mixed in a molar ratio of 1:1:1:1:1; preferably, in the ZrSi2 and Si mixed powder, the molar ratio of ZrSi2 to Si is (1~2):1; preferably, the particle size of the high-entropy silicide alloy powder, the ZrSi2 and Si mixed powder and the silicon powder are all 1~10μm.

[0015] Preferably, in step (4), the phased heating reaction infiltration involves placing the first composite material in the three-temperature zone isolation fixture and heating it as a whole, performing the following three phases of reaction infiltration sequentially: the first phase of reaction infiltration involves heating at a rate of 5~8℃ / min to 1400~1480℃ for 1.5~2.5h; the second phase of reaction infiltration involves heating at a rate of 3~5℃ / min to 1650~1750℃ for 1.5~2h; and the third phase of reaction infiltration involves heating at a rate of 2~4℃ / min to 1900~2100℃ for 2~4h. Preferably, all three phases of reaction infiltration are performed under an absolute pressure ≤10Pa. Preferably, after the third phase of reaction infiltration is completed, the material is first cooled to 800℃ in the furnace, and then argon gas is used for further cooling.

[0016] Preferably, in step (5): the heat preservation treatment time is 2~4 hours; and / or the carbon fiber reinforced ceramic matrix composite material has a density gradient along the thickness direction, and the density of the outer layer is 2.7~2.82 g / cm³. 3 The density of the inner layer is 2.0~2.3 g / cm³. 3 .

[0017] In a third aspect, the present invention provides a gradient-modified carbon fiber reinforced ceramic matrix composite material prepared by the preparation method described in the second aspect of the present invention.

[0018] Compared with the prior art, the present invention has at least the following beneficial effects: (1) Although the prior art CN115385712A discloses a high-entropy ultra-high temperature ceramic matrix composite material and its preparation method, the uniform distribution of high-entropy ceramics leads to problems such as increased structural weight and wasted performance. However, the present invention innovatively designs a gradient structure, so that the high-entropy ceramics are enriched in the outer layer (for example, accounting for 30~40% of the total thickness), while the inner layer remains a SiC matrix (accounting for 10~30% of the total thickness). In this way, the structural weight can be reduced while ensuring the material's resistance to ultra-high temperature ablation at 2300℃. The density gradient range can be controlled within 2.0~2.82 g / cm³. 3 The range is further reduced compared to existing uniform distribution schemes, achieving synergistic optimization of ultra-high temperature protection and structural lightweighting.

[0019] (2) The existing technology CN110627517B lacks a gradient design of ceramic components. However, this invention achieves a gradient distribution of ceramic components in a single component simultaneously through partitioned directional reactive melting infiltration technology. The outer layer is a high-density, high-entropy ceramic (density, for example, 2.7~2.82 g / cm³). 3 It can withstand the scouring of ultra-high temperature airflows up to 2300℃, the middle layer achieves a continuous transition of ceramic components, and the inner layer is a low-density matrix (density, for example, 2.0~2.3 g / cm³). 3 This gradient design reduces the modulus to alleviate stress concentration, and the coefficient of thermal expansion changes continuously, effectively avoiding crack initiation and ablation layer peeling caused by sudden changes in interfacial thermal stress.

[0020] (3) The existing technology CN108585906B has limitations in reactive infiltration, which makes it difficult to achieve controllable introduction and gradient distribution of high-entropy ceramics and easily causes fiber damage. However, this invention develops a phased and layered temperature-increasing reactive infiltration process: the first stage is low-temperature silicon infiltration to form an inner SiC matrix; the second stage is medium-temperature medium-entropy alloy infiltration to construct a transition layer; and the third stage is high-temperature infiltration to form an outer (Zr, Hf, Ta, Nb, Ti)C matrix. x The high-entropy carbide solid solution, with its three-temperature-zone isolation fixture, ensures that the melts in different temperature zones do not mix. By naturally adsorbing the melt through porosity differences, it achieves precise gradient distribution and stoichiometric control of ceramic components, while avoiding segregation of high-entropy components and fiber damage.

[0021] (4) The present invention uses a variable density needle punching process to construct a carbon fiber preform with a gradient pore structure. The porosity of the near-ablation end of the carbon fiber preform is, for example, 50~60%, and the porosity of the far-ablation end is, for example, 15~25%. Capillary action is used to achieve spontaneous gradient pre-distribution of the high-entropy ceramic precursor (a complex of high-entropy carbide ceramic particles and cracked carbon in nanocomposite sol) along the thickness direction. Combined with the impregnation-curing-cracking process and the phased heating reaction melting infiltration, the efficiency of introducing high-entropy ceramics is significantly improved, and the homogenization of the high-entropy carbide solid solution components (i.e., uniform solid solution of the five metal elements in the carbide lattice and uniform distribution in the planar direction) is promoted. Thus, a gradient distribution in the thickness direction and a homogeneous distribution in the planar direction are formed in the overall material, avoiding the structural weight increase and performance waste caused by the overall uniform distribution, and realizing the synergistic improvement of ultra-high temperature ablation resistance and high temperature mechanical properties. Attached Figure Description

[0022] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort. The drawings of the present invention are provided for illustrative purposes only, and the scale, size, etc. of the parts in the drawings may not be consistent with the actual product.

[0023] Figure 1 This is a schematic diagram of the structure of gradient-modified carbon fiber reinforced ceramic matrix composite material in some specific embodiments of the present invention; Figure 2 This is a schematic diagram of gradient-modified carbon fiber reinforced ceramic matrix composite material placed in a three-temperature zone isolation fixture in some specific embodiments of the present invention. Detailed Implementation

[0024] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some, not all, of the embodiments of this invention. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0025] In a first aspect, the present invention provides a gradient-modified carbon fiber reinforced ceramic matrix composite material (abbreviated as carbon fiber reinforced ceramic matrix composite material or gradient composite material), wherein the carbon fiber reinforced ceramic matrix composite material comprises, sequentially from the near-ablation end to the far-ablation end along the thickness direction (Z direction), an outer layer, a middle layer, and an inner layer, for example, such as Figure 1As shown; the outer layer is a near-ablation surface layer, and the outer layer matrix phase contains (Zr, Hf, Ta, Nb, Ti)C. x The high-entropy carbide solid solution and the SiC accompanying phase generated in situ during the preparation process, i.e., the outer matrix phase, contain (Zr, Hf, Ta, Nb, Ti)C. x In this invention, a high-entropy carbide solid solution serves as the main phase, and in-situ generated SiC serves as the auxiliary phase. The outer matrix phase is primarily (Zr, Hf, Ta, Nb, Ti)C. x High-entropy carbide solid solution, (Zr,Hf,Ta,Nb,Ti)C x The volume fraction of the high-entropy carbide solid solution is 85%–95%, and the volume fraction of the in-situ generated SiC associated phase is 5%–15%. In this invention, the outer matrix phase can be denoted as (Zr,Hf,Ta,Nb,Ti)C. x -SiC forms a high-entropy ceramic enrichment region, which can utilize the high melting point (>3500℃) and low oxygen diffusion coefficient of high-entropy ceramics to provide ultra-high temperature ablation protection above 2300℃; in the (Zr,Hf,Ta,Nb,Ti)C x In the high-entropy carbide solid solution, 0.8 ≤ x ≤ 1.2; the middle layer (also referred to as the intermediate layer or transition layer) matrix phase is ZrC-SiC, in other words, the middle layer matrix phase is composed of ZrC (zirconium carbide) and SiC (silicon carbide). This middle layer can achieve a continuous transition between ceramic components and modulus, relieving thermal stress; the inner layer is the far-ablation surface layer, and the inner layer matrix phase is SiC, forming a low-modulus, high-toughness layer. By reducing the modulus, stress concentration is relieved, and the overall mechanical properties of the composite material are improved; the reinforcement of the carbon fiber reinforced ceramic matrix composite material is a carbon fiber preform with a gradient porosity structure along the thickness direction; in this invention, the carbon fiber preform with a gradient porosity structure is, for example, a carbon fiber needle-punched structure preform with a gradient porosity structure; in this invention, the thickness direction refers to the Z-direction perpendicular to the ablation surface during material service, pointing from the near-ablation end to the far-ablation end.

[0026] The gradient-modified carbon fiber reinforced ceramic matrix composite material of this invention has dual gradient modification of preform structure and ceramic components, which solves the problems of single distribution of ceramic components, limited gradient structure and difficulty in balancing ultra-high temperature ablation resistance and mechanical properties in the prior art.

[0027] According to some preferred embodiments, the thickness of the outer layer accounts for 30-40% (e.g., 32%, 35%, 38% or 40%) of the total thickness of the carbon fiber reinforced ceramic matrix composite; the thickness of the middle layer accounts for 40-50% (e.g., 42%, 45%, 47% or 50%) of the total thickness of the carbon fiber reinforced ceramic matrix composite; and the thickness of the inner layer accounts for 10-30% (e.g., 10%, 20% or 30%) of the total thickness of the carbon fiber reinforced ceramic matrix composite.

[0028] In a second aspect, the present invention provides a method for preparing gradient-modified carbon fiber reinforced ceramic matrix composites, the method comprising the following steps: (1) A carbon fiber preform with a gradient pore structure (also referred to as a gradient preform) is prepared by a variable density needle punching process. (2) A pyrolytic carbon interface layer (PyC interface layer) is deposited on the carbon fiber surface of the carbon fiber preform with a gradient pore structure to obtain a low-density C / C porous preform; (3) Prepare a nanocomposite sol containing five kinds of high-entropy carbide ceramic particles and thermosetting phenolic resin, and use the nanocomposite sol as an impregnation liquid to perform an impregnation-curing-pyrolysis process on the low-density C / C porous preform, so that the high-entropy ceramic precursor is pre-distributed in a gradient along the thickness direction to obtain the first composite material; the high-entropy ceramic precursor is a composite of high-entropy carbide ceramic particles and pyrolyzed carbon; In this invention, the nanocomposite sol containing five types of high-entropy carbide ceramic particles and thermosetting phenolic resin is, for example, a nanocomposite sol containing ZrC, HfC, TaC, NbC, and TiC nanoparticles; step (3) utilizes the capillary effect difference of the gradient pore structure to form an outer layer enriched gradient load along the thickness direction of the nanocomposite sol during the overall impregnation process, realizing the gradient pre-distribution of high-entropy ceramic precursor and high-entropy carbide ceramic particles enriched in the outer layer along the thickness direction. The pre-distributed high-entropy carbide ceramic particles are then used in the subsequent high-temperature melting and infiltration stage. The segment serves as a heterogeneous nucleation site, promoting the reaction kinetics between the high-entropy silicide alloy melt and the carbon matrix, and suppressing alloy residue and component segregation. Simultaneously, the high-entropy carbide ceramic particles form a physical isolation layer on the fiber surface, which can buffer the volume expansion stress during carbide formation and reduce the risk of fiber damage. This invention has found that without this step, the lack of pre-distributed nucleating agent will lead to high reaction activation energy and reaction lag, which will easily cause alloy residue and component segregation. Moreover, relying solely on high-temperature melting and infiltration is insufficient to guarantee the preferential enrichment and gradient distribution effect of the outer high-entropy carbide solid solution.

[0029] (4) The first composite material is placed in a three-temperature zone isolation fixture and subjected to zoned and staged heating reaction melting infiltration to obtain a second composite material including an inner matrix phase, a middle matrix phase and an outer matrix phase; In this invention, the three-temperature zone isolation fixture is, for example, a three-temperature zone isolation graphite fixture; the zoned and staged heating refers to using a three-temperature zone isolation fixture to divide the material into zones, while the heating process is an overall programmed heating, and the different temperature zones of the powder are sequentially brought to the melting infiltration temperature by controlling the heating stages; In this invention, the gradient melting infiltration of ceramic components is achieved through the zoned directional reaction melting infiltration in step (4). Since the reaction melting infiltration process mainly fills the pores rather than significantly changes the macroscopic size of the material, the thickness ratio of each region of the preform is basically consistent with the thickness ratio of the outer, middle and inner layers of the final composite material; (5) The second composite material is subjected to heat treatment at 1600~1800℃ (e.g., 1600℃, 1650℃, 1700℃, 1750℃ or 1800℃) under the protection of an inert gas (e.g. argon) to obtain a gradient-modified carbon fiber reinforced ceramic matrix composite material; In step (5) of this invention, the heat treatment at 1600~1800℃ can eliminate residual stress from melting and infiltration and promote the homogenization of the high-entropy carbide solid solution; The carbon fiber reinforced ceramic matrix composite material obtained by this invention includes an outer layer, a middle layer and an inner layer along the thickness direction from the near ablation end to the far ablation end; The outer layer is the near ablation surface layer, and the matrix phase of the outer layer is (Zr,Hf,Ta,Nb,Ti)C x -SiC; the middle matrix phase is ZrC-SiC; the inner layer is a far-ablation surface layer, and the inner matrix phase is SiC; the reinforcement of the carbon fiber reinforced ceramic matrix composite material is a carbon fiber preform with a gradient pore structure along the thickness direction.

[0030] Chinese patent application CN114380613A discloses a method for preparing an axially gradient and planar homogeneous ultra-high temperature ceramic matrix composite material. However, it introduces the ceramic phase by puncturing and pre-drilling holes. The ultra-high temperature ceramic is limited to single or simple combination systems such as ZrC, HfC, and TaC. The ablation resistance and long-term thermal stability under extreme high temperature oxidation environment need to be improved. Moreover, it relies on puncturing and pre-drilling holes for physical implantation of ceramic rods / metal rods, which makes it difficult to achieve nanoscale component pre-distribution and component homogenization. Furthermore, the puncturing process causes mechanical damage to the fiber bundles, affecting the high temperature mechanical properties of the material. This invention resolves the contradiction between high-entropy carbide high-temperature synthesis and fiber protection through the combined effect of high-entropy carbide ceramic particle pre-distribution and phased heating reaction melting infiltration. It achieves in-situ synthesis of high-entropy carbides and their synergistic integration with continuous fibers while avoiding excessive erosion of carbon fibers, thus balancing the introduction of high-entropy ceramic phase gradients with material mechanical properties. This invention discovers that step (3) utilizes the capillary effect difference of the gradient pore structure to achieve outer-layer enrichment of the nanocomposite sol along the thickness direction during the overall impregnation process, realizing a gradient pre-distribution of high-entropy carbide ceramic particles along the thickness direction. These pre-distributed high-entropy carbide ceramic particles act as nucleating agents in the subsequent high-temperature melting infiltration stage above 1900℃, effectively... The alloy residue and component segregation caused by reaction lag are suppressed. At the same time, the high-entropy carbide ceramic nanoparticles form a physical isolation layer on the fiber surface to buffer the volume expansion stress during carbide formation. In step (4), the inner matrix phase, middle matrix phase and outer matrix phase are constructed in stages through three temperature zones. During the final overall heating to above 1900℃, the pre-formed inner matrix phase and middle matrix phase have a dense microstructure and can be used as a reaction barrier layer to block the penetration of high-entropy alloy melt into the material interior, confining the high-entropy carbide formation reaction to the outer region. At the same time, it remains chemically stable at high temperature, effectively protecting the internal carbon fibers from direct erosion and thermal damage by the molten high-entropy silicide alloy.

[0031] This invention innovatively designs a gradient structure, which enriches high-entropy ceramics in the outer layer (e.g., accounting for 30-40% of the total thickness), while the inner layer remains a SiC matrix (accounting for 10-30% of the total thickness). This reduces the structural weight while ensuring the material's resistance to ultra-high temperature ablation up to 2300℃. The density gradient range can be controlled within 2.0-2.82 g / cm³. 3 Compared to existing uniform distribution schemes, this invention achieves further weight reduction, realizing synergistic optimization of ultra-high temperature protection and structural lightweighting. Through zoned directional reactive infiltration technology, this invention simultaneously achieves a gradient distribution of ceramic components within a single component, with the outer layer being a high-density, high-entropy ceramic (density, for example, 2.7~2.8 g / cm³). 3It can withstand the scouring of ultra-high temperature airflows up to 2300℃, the middle layer achieves a continuous transition of ceramic components, and the inner layer is a low-density matrix (density, for example, 2.0~2.3 g / cm³). 3 This gradient design reduces the modulus to alleviate stress concentration, and the coefficient of thermal expansion changes continuously, effectively avoiding crack initiation and ablation layer peeling caused by sudden changes in interfacial thermal stress.

[0032] According to some preferred embodiments, the thickness of the outer layer accounts for 30-40% of the total thickness of the carbon fiber reinforced ceramic matrix composite material; the thickness of the middle layer accounts for 40-50% of the total thickness of the carbon fiber reinforced ceramic matrix composite material; and the thickness of the inner layer accounts for 10-30% of the total thickness of the carbon fiber reinforced ceramic matrix composite material. In this invention, apart from the thickness of the outer layer and the middle layer, the remaining thickness of the carbon fiber reinforced ceramic matrix composite material is the thickness of the inner layer, that is, the sum of the thicknesses of the outer layer, the middle layer and the inner layer is equal to the total thickness of the carbon fiber reinforced ceramic matrix composite material.

[0033] According to some preferred embodiments, in step (1): the carbon fiber preform has a gradient porosity structure along the thickness direction; when the carbon fiber preform is prepared using a variable density needle punching process, the preform region used to form the outer layer of the carbon fiber reinforced ceramic matrix composite material can, for example, use a puncture needle with a diameter of 0.35~0.45 mm (e.g., 0.35, 0.40 or 0.45 mm), and the needle punching density is 45~55 needles / cm. 2 (e.g., 45, 48, 50, 52 or 55 thorns / cm) 2 The interlayer density is 0.6~0.8 g / cm³. 3 (e.g., 0.6, 0.7 or 0.8 g / cm³) 3 The porosity is 50-60% (e.g., 50%, 55%, or 60%). The preform region used to form the middle layer of the carbon fiber reinforced ceramic matrix composite can, for example, employ a puncture needle with a diameter of 0.20-0.30 mm (e.g., 0.20, 0.25, or 0.30 mm) and a puncture density of 25-35 punctures / cm². 2 (e.g., 25, 28, 30, 32 or 35 thorns / cm) 2 The interlayer density is 0.9~1.1 g / cm³. 3 (e.g., 0.9, 1.0 or 1.1 g / cm³) 3 The porosity is 30-40% (e.g., 30%, 35%, or 40%). The preform regions used to form the inner layer of the carbon fiber reinforced ceramic matrix composite can, for example, employ puncture needles with a diameter of 0.10-0.18 mm (e.g., 0.10, 0.15, or 0.18 mm) and a puncture density of 15-25 punctures / cm². 2(e.g., 15, 18, 20, 22 or 25 thorns / cm) 2 The interlayer density is 1.2~1.4 g / cm³. 3 (e.g., 1.2, 1.3 or 1.4 g / cm³) 3 The porosity is 15-25% (e.g., 15%, 20%, or 25%). In this invention, the overall fiber volume content of the carbon fiber preform can be controlled, for example, at 28-35% (e.g., 28%, 30%, 32%, or 35%), with the fiber volume content increasing gradually from the outer layer to the inner layer.

[0034] This invention employs a variable-density needle punching process to construct a carbon fiber preform with a gradient porosity structure. The porosity of the carbon fiber preform near the ablation end is, for example, 50-60%, and the porosity of the far-from-ablation end is, for example, 15-25%. Capillary action is used to achieve a spontaneous gradient pre-distribution of the high-entropy ceramic precursor. Combined with an impregnation-curing-pyrolysis process and a zoned, staged heating reaction melting process, the introduction efficiency and distribution uniformity of the high-entropy ceramic are significantly improved. This is beneficial for achieving a synergistic improvement in ultra-high temperature ablation resistance and high-temperature mechanical properties, which is significantly superior to existing composite materials with a single gradient or uniform distribution.

[0035] According to some preferred embodiments, in step (2): the pyrolytic carbon interface layer (PyC interface layer) is deposited by chemical vapor infiltration; the thickness of the pyrolytic carbon interface layer is 200~500 nm (e.g., 200, 300, 400 or 500 nm) to buffer the thermal expansion mismatch between the fibers and the ceramic matrix; and / or the density of the low-density C / C porous preform is 1.10~1.40 g / cm³. 3 .

[0036] According to some preferred embodiments, in step (3): the nanocomposite sol is uniformly mixed from high-entropy carbide ceramic particles, thermosetting phenolic resin, hexamethylenetetramine, dispersant and solvent. The high-entropy carbide ceramic particles are composed of ZrC (zirconium carbide) nanoparticles, HfC (hafnium carbide) nanoparticles, TaC (tantalum carbide) nanoparticles, NbC (niobium carbide) nanoparticles and TiC (titanium carbide) nanoparticles in a molar ratio of 1:1:1:1:1. The dispersant is polyvinyl butyral (PVB) and / or a silane coupling agent, and the solvent is anhydrous ethanol and / or acetone. In this invention, the high-entropy carbide ceramic particles refer to ZrC, HfC, TaC, NbC, TiC, and TiC nanoparticles. C nanoparticles are used, employing a nanocomposite sol containing high-entropy carbide ceramic particles and thermosetting phenolic resin as the impregnation liquid. After an impregnation-curing-pyrolysis process, the high-entropy carbide ceramic particles are pyrolyzed and anchored in situ within the pores, forming a complex with the pyrolyzed carbon formed by the thermosetting phenolic resin. This results in a gradient-predistributed high-entropy ceramic precursor and high-entropy carbide ceramic particles in the obtained first composite material. The high-entropy carbide ceramic particles provide heterogeneous nucleation sites for subsequent high-temperature melting and infiltration. This invention does not specifically limit the thermosetting phenolic resin, polyvinyl butyral, etc., and commercially available products can be used. In some specific embodiments, the thermosetting phenolic resin can be, for example, PFJ. Y-5121 or 2130 type thermosetting phenolic resin; preferably, the particle size (average particle size) of ZrC nanoparticles, HfC nanoparticles, TaC nanoparticles, NbC nanoparticles and / or TiC nanoparticles is 50~200nm (e.g. 50, 100, 150 or 200nm); preferably, the residual carbon content of the thermosetting phenolic resin is 40~50% (e.g. 40%, 45% or 50%); preferably, the solvent is a mixture of anhydrous ethanol and acetone in a volume ratio of 1:(0.5~1.5) (e.g. 1:0.5, 1:1 or 1:1.5); preferably, the mass ratio of the high-entropy carbide ceramic particles to the thermosetting phenolic resin is (3~5). The ratio of the thermosetting phenolic resin to hexamethylenetetramine is (10-15):1 (e.g., 10:1, 12:1, or 15:1), and the ratio of the high-entropy carbide ceramic particles to the dispersant is (20-30):1 (e.g., 20:1, 25:1, or 30:1). Preferably, the solid content of the nanocomposite sol is 30-40 wt% (e.g., 30 wt%, 35 wt%, or 40 wt%). In this invention, the solid content of the nanocomposite sol refers to the sum of the mass percentages of the high-entropy carbide ceramic particles, thermosetting phenolic resin, hexamethylenetetramine, and dispersant in the nanocomposite sol.

[0037] This invention uses the aforementioned nanocomposite sol as an impregnation solution for an impregnation-curing-pyrolysis process, primarily to facilitate the subsequent melting and infiltration of (Zr,Hf,Ta,Nb,Ti)C. x High-entropy carbide solid solutions provide uniformly distributed nucleation sites, and primarily suppress the macroscopic aggregation of high-entropy carbides in subsequent reactions. This invention prepares a nanocomposite sol by compounding high-entropy carbide ceramic nanoparticles with thermosetting phenolic resin and introducing hexamethylenetetramine as a curing agent. The nanoscale ceramic powder (50-200 nm) ensures good flowability and permeability of the sol, facilitating its entry into the micropores within the fiber bundles. The thermosetting phenolic resin, as a carbon source and binder with a high residual carbon rate (40-50%), crosslinks and anchors the ceramic particles at low temperatures under the action of the curing agent. After pyrolysis, a continuous carbon network is formed, fixing the high-entropy components in situ within the pores. This avoids the low yield and insufficient macropore filling of simple polymer precursor ceramics, and overcomes the limitations of simple powder slurries. The invention addresses the issues of poor material permeability and uneven distribution. Simultaneously, the high specific surface area of ​​the formed high-entropy carbide ceramic particles provides abundant nucleation sites for subsequent high-temperature melting and infiltration, promoting the homogenization of the high-entropy carbide solid solution. Preferably, the mass ratio of the high-entropy carbide ceramic particles to the thermosetting phenolic resin is controlled at (3~5):1. This ensures the firm anchoring of the nanoparticles by the cracked carbon in the thermosetting phenolic resin and the stability of the gradient structure, while also preserving unobstructed pore channels for subsequent reaction melting and infiltration. If this ratio is too low, excessive cracked carbon in the thermosetting phenolic resin will clog the pores, hindering the subsequent infiltration of the high-entropy silicide alloy melt. Conversely, if this ratio is too high, the thermosetting phenolic resin will be insufficient to effectively bond and anchor the ceramic particles, hindering the effective formation of the gradient pre-distribution structure.

[0038] According to some preferred embodiments, the impregnation-curing-pyrolysis process is repeated 2 to 4 times. In each impregnation-curing-pyrolysis process, the impregnation is vacuum impregnation, carried out under an absolute pressure ≤100 Pa (e.g., 50, 80, or 100 Pa), the impregnation time is 30 to 60 min (e.g., 30, 45, or 60 min), the curing is carried out at 80 to 120 °C (e.g., 80, 100, or 120 °C) for 2 to 4 h (e.g., 2, 3, or 4 h), and the pyrolysis is carried out at 900 to 1000 °C (e.g., 900, 950, or 1000 °C) for 1 to 3 h (e.g., 1, 2, or 3 h). In this invention, the pyrolysis is carried out, for example, under an argon atmosphere. In this invention, the impregnation-curing-pyrolysis process can convert thermosetting phenolic resin into amorphous carbon (pyrolyzed carbon) for fixing high-entropy carbide ceramic particles.

[0039] According to some preferred embodiments, in step (4): the inner cavity of the three-temperature zone isolation fixture (along the thickness direction of the carbon fiber reinforced ceramic matrix composite material) sequentially includes a high-temperature zone for filling high-entropy silicide alloy powder, a medium-temperature zone for filling a mixture of ZrSi2 (zirconium disilicide) and Si (silicon) powder, and a low-temperature zone for filling silicon powder. The high-temperature zone, medium-temperature zone, and low-temperature zone are isolated from each other and are three independent filling zones. This directional isolation ensures that the melts in different zones do not mix during the reaction infiltration process. For example, ... Figure 2 As shown; in this invention, the silicon powder used can be, for example, silicon powder with a particle size of 1~10μm and a purity >99%; the high-entropy silicide alloy powder filled in the high-temperature zone is used to form the outer matrix phase of the carbon fiber reinforced ceramic matrix composite material after reactive melting and infiltration; the ZrSi2 and Si mixed powder filled in the medium-temperature zone is used to form the middle matrix phase of the carbon fiber reinforced ceramic matrix composite material after reactive melting and infiltration; the silicon powder filled in the low-temperature zone is used to form the inner matrix phase of the carbon fiber reinforced ceramic matrix composite material after reactive melting and infiltration; the high-entropy silicide alloy powder is composed of ZrSi2 (zirconium disilicide) powder. The powder is composed of HfSi2 (hafnium disilicide) powder, TaSi2 (tantalum disilicide) powder, NbSi2 (niobium disilicide) powder, and TiSi2 (titanium disilicide) powder mixed in a molar ratio of 1:1:1:1:1. Preferably, the molar ratio of ZrSi2 to Si in the ZrSi2 and Si mixed powder is (1~2):1. Preferably, the particle size of the high-entropy silicide alloy powder, the ZrSi2 and Si mixed powder, and the silicon powder is 1~10μm (e.g., 1, 4, 7, 10μm). If the particle size is too large, the melting and infiltration efficiency will be reduced; if it is too small, it will be easily oxidized and difficult to disperse.

[0040] According to some preferred embodiments, in step (4), the phased heating reaction infiltration involves placing the first composite material in the three-temperature zone isolation fixture and heating it as a whole, performing the following three phases of reaction infiltration sequentially: The first phase of reaction infiltration involves heating at a rate of 5~8℃ / min (e.g., 5℃ / min, 6℃ / min, 7℃ / min or 8℃ / min) to 1400~1480℃ (e.g., 1400℃, 1450℃ or 1480℃) for 1.5~2.5h (e.g., 1.5, 2.0 or 2.5h); in this first phase of reaction infiltration, pure silicon powder melts and infiltrates into the inner layer of the material to form a SiC matrix; the second phase of reaction infiltration involves continuing to heat at a rate of 3~5℃ / min (e.g., 3℃ / min, 4℃ / min or 5℃ / min) to 16℃. The reaction infiltration process involves reacting and infiltrating at 50~1750℃ (e.g., 1650℃, 1700℃, or 1750℃) for 1.5~2h (e.g., 1.5, 1.8, or 2.0h); in this second stage of reaction infiltration, the ZrSi2 and Si mixed powder melts and infiltrates into the middle layer of the material to form a ZrC-SiC matrix phase; the third stage of reaction infiltration involves continuing to heat at a rate of 2~4℃ / min (e.g., 2℃ / min, 3℃ / min, or 4℃ / min) to 1900~2100℃ (e.g., 1900℃, 1950℃, 2000℃, 2050℃, or 2100℃) for 2~4h (e.g., 2, 3, or 4h); in this third stage of reaction infiltration, the high-entropy silicide alloy powder melts and infiltrates into the outer layer of the material (outer ablation-resistant layer) and reacts with the carbon matrix to form (Zr,Hf,Ta,Nb,Ti)C. x -SiC outer matrix phase; preferably, the three-stage reaction melting and infiltration are all carried out under an absolute pressure ≤10Pa (e.g., 2, 5, 8 or 10Pa); preferably, after the third-stage reaction melting and infiltration is completed, the furnace is first cooled to 800°C, and then argon gas is applied for cooling (argon gas rapid cooling); the present invention does not limit the specific operation of argon gas cooling, and those skilled in the art can make conventional choices; in some specific embodiments of the present invention, for example, after the third-stage reaction melting and infiltration is completed, the furnace is first cooled to 800°C, and then argon gas is applied for cooling to 200~300°C before being taken out of the furnace, and then naturally cooled to room temperature in air (e.g., room temperature 15~35°C).

[0041] According to some preferred embodiments, in step (5): the heat preservation treatment time is 2~4 hours (e.g., 2, 3 or 4 hours); and / or the carbon fiber reinforced ceramic matrix composite material has a density gradient along the thickness direction (the overall density of the composite material is gradient-distributed), and the density of the outer layer is 2.7~2.82 g / cm³. 3 (e.g., 2.7, 2.75, 2.8 or 2.82 g / cm³) 3 The density of the inner layer is 2.0~2.3 g / cm³.3 (e.g., 2.0, 2.1, 2.2 or 2.3 g / cm³) 3 The overall density of the carbon fiber reinforced ceramic matrix composite material obtained by this invention ranges from 2.30 to 2.82 g / cm³. 3 (e.g., 2.30, 2.50, 2.65, 2.80 or 2.82 g / cm³) 3 ).

[0042] In a third aspect, the present invention provides a gradient-modified carbon fiber reinforced ceramic matrix composite material prepared by the preparation method described in the second aspect of the present invention.

[0043] The present invention will be further described below by way of examples, but the scope of protection of the present invention is not limited to these embodiments. The present invention may have many other embodiments, and those skilled in the art can make various corresponding changes and modifications based on the present invention without departing from its spirit and essence. However, all such corresponding changes and modifications should fall within the scope of protection of the appended claims. Unless otherwise specified, the experimental methods used in the following embodiments and comparative examples are conventional methods. Unless otherwise specified, the materials used in the following embodiments and comparative examples are commercially available.

[0044] Example 1 ① Preparation of carbon fiber preforms with gradient porosity along the thickness direction: T800-12K carbon fiber was used, and the preforms were prepared by a variable density needle punching process. The preparation parameters were as follows: the preform region used to form the outer layer of the carbon fiber reinforced ceramic matrix composite (accounting for 30% of the total thickness of the carbon fiber preform with gradient porosity, which is consistent with the outer layer thickness ratio of the final gradient modified carbon fiber reinforced ceramic matrix composite) used a puncture needle with a diameter of 0.40 mm and a needle punching density of 50 needles / cm². 2 The interlayer density is 0.7 g / cm³. 3 The porosity is 55%. The preform region used to form the middle layer of the carbon fiber reinforced ceramic matrix composite (accounting for 40% of the total thickness of the carbon fiber preform with a gradient porosity structure, this percentage being consistent with the thickness percentage of the middle layer of the finally obtained gradient-modified carbon fiber reinforced ceramic matrix composite) is pierced using a 0.25 mm diameter needle with a piercing density of 30 punctures / cm². 2 The interlayer density is 1.0 g / cm³. 3 The porosity is 35%. The preform region used to form the inner layer of the carbon fiber reinforced ceramic matrix composite (accounting for 30% of the total thickness of the carbon fiber preform with a gradient porosity structure, this percentage being consistent with the thickness percentage of the inner layer of the finally obtained gradient-modified carbon fiber reinforced ceramic matrix composite) is pierced using a 0.15 mm diameter needle with a piercing density of 20 punctures / cm².2 The interlayer density is 1.3 g / cm³. 3 The porosity is 20%, the thickness of the carbon fiber preform with gradient pore structure is 20 mm, and the fiber volume content is 32%.

[0045] ② Preparation of low-density C / C porous preform: A pyrolytic carbon interface layer (PyC interface layer) is deposited on the carbon fiber surface of a carbon fiber preform with a gradient pore structure via chemical vapor infiltration (CVI) to form a low-density C / C porous preform. The deposition parameters for CVI are as follows: gas source is C3H6 (propylene) and N2 (nitrogen), C3H6 to N2 volume ratio is 1:4, deposition temperature is 1000℃, deposition pressure (absolute pressure) is 3kPa, deposition time is 100h, PyC interface layer thickness is 350nm, and the density of the low-density C / C porous preform is 1.25g / cm³. 3 .

[0046] ③ Preparation of the first composite material: A nanocomposite sol containing five types of high-entropy carbide ceramic particles and thermosetting phenolic resin was prepared. The low-density C / C porous preform was impregnated, cured, and pyrolyzed using the nanocomposite sol as the impregnation liquid, resulting in a gradient pre-distribution of the high-entropy ceramic precursor along the thickness direction, thus obtaining the first composite material. The nanocomposite sol is composed of high-entropy carbide ceramic particles, thermosetting phenolic resin (PFJY-5121 type thermosetting phenolic resin with a residual carbon rate of 45%), hexamethylenetetramine, polyvinyl butyral (PVB), and a solvent, mixed uniformly. The high-entropy carbide ceramic particles are composed of ZrC (zirconium carbide) nanoparticles, HfC (hafnium carbide) nanoparticles, TaC (tantalum carbide) nanoparticles, NbC (niobium carbide) nanoparticles, and TiC (titanium carbide) nanoparticles in a molar ratio of 1:1:1:1:1:1. The average particle size of aC nanoparticles, NbC nanoparticles, and TiC nanoparticles is 100 nm. The solvent is a mixture of anhydrous ethanol and acetone in a volume ratio of 1:1. The mass ratio of high-entropy carbide ceramic particles to thermosetting phenolic resin is 4:1, the mass ratio of thermosetting phenolic resin to hexamethylenetetramine is 12:1, the mass ratio of high-entropy carbide ceramic particles to polyvinyl butyral is 25:1, and the solid content of the nanocomposite sol is 35 wt%. The number of cycles of the impregnation-curing-pyrolysis process (i.e., the number of times the impregnation, curing, and pyrolysis processes are repeated) is 3. In each impregnation-curing-pyrolysis process, the impregnation is vacuum impregnation, which is carried out under an absolute pressure of 80 Pa for 45 min. The curing is carried out at 100 °C for 3 h, and the pyrolysis is carried out at 950 °C for 2 h under an argon atmosphere.

[0047] ④ Sectional and phased temperature-intensity directional reaction melting infiltration: The first composite material is placed in a three-temperature zone isolation fixture and subjected to sectional and phased temperature-intensity reaction melting infiltration to obtain an inner matrix phase SiC, a middle matrix phase ZrC-SiC, and an outer matrix phase (Zr,Hf,Ta,Nb,Ti)C. x -SiC second composite material; wherein, the inner cavity of the three-temperature zone isolation fixture includes, along the thickness direction of the carbon fiber reinforced ceramic matrix composite material, a high-temperature zone for filling high-entropy silicide alloy powder, a medium-temperature zone for filling ZrSi2 and Si mixed powder, and a low-temperature zone for filling silicon powder, wherein the high-temperature zone, the medium-temperature zone, and the low-temperature zone are isolated from each other; the high-entropy silicide alloy powder filled in the high-temperature zone is used to form the outer matrix phase (Zr,Hf,Ta,Nb,Ti)C of the carbon fiber reinforced ceramic matrix composite material after reactive melting and infiltration. x -SiC, the ZrSi2 and Si mixed powder filled in the medium-temperature zone is used to form the middle matrix phase ZrC-SiC of the carbon fiber reinforced ceramic matrix composite after reaction melting and infiltration, and the silicon powder (average particle size 5μm, purity >99%) filled in the low-temperature zone is used to form the inner matrix phase SiC of the carbon fiber reinforced ceramic matrix composite after reaction melting and infiltration; the high-entropy silicide alloy powder is composed of ZrSi2 powder, HfSi2 powder, TaSi2 powder, NbSi2 powder and TiSi2 powder mixed in a molar ratio of 1:1:1:1:1 (the average particle size of ZrSi2 powder, HfSi2 powder, TaSi2 powder, NbSi2 powder and TiSi2 powder are all 5μm, and the purity is all >99%); in the ZrSi2 and Si mixed powder, ZrSi2 and Si (ZrSi The molar ratio of the powder and silicon powder (both with an average particle size of 5 μm and a purity >99%) is 1.5:1. The phased heating reaction infiltration process involves placing the first composite material in the three-temperature zone isolation fixture and heating it as a whole, performing the following three stages of reaction infiltration sequentially: the first stage reaction infiltration involves heating to 1450℃ at a heating rate of 6℃ / min for 2 hours; the second stage reaction infiltration involves heating to 1700℃ at a heating rate of 4℃ / min for 1.8 hours; and the third stage reaction infiltration involves heating to 2000℃ at a heating rate of 3℃ / min for 3 hours. All three stages of reaction infiltration are carried out under an absolute pressure of 5 Pa. After the third stage reaction infiltration is completed, the material is first cooled to 800℃ in the furnace, then purged with argon gas and cooled to 200℃ before being removed from the furnace and then naturally cooled to room temperature in air.

[0048] ⑤ The second composite material was heated at 1700℃ for 3 hours under argon protection to obtain a gradient-modified carbon fiber reinforced ceramic matrix composite material.

[0049] Performance testing: The outer layer density of the gradient-modified carbon fiber reinforced ceramic matrix composite was measured to be 2.75 g / cm³. 3 The inner layer density is 2.15 g / cm³. 3 Oxyacetylene ablation tests were conducted according to GJB 323B-2018 standard. The material surface temperature was 2300℃, the test time was 300s, and the measured linear ablation rate was 5.83×10⁻⁶. -4 mm / s; the bending strength measured in air at 1600℃ according to GJB 10311-2021 standard is 245MPa.

[0050] Example 2 Example 2 is basically the same as Example 1, except that: In step ①, the needle density of the preform region used to form the outer layer of the carbon fiber reinforced ceramic matrix composite is 45 needles / cm. 2 The needle density of the preform region used to form the inner layer of the carbon fiber reinforced ceramic matrix composite is 25 needles / cm². 2 .

[0051] In step ④, the third stage of reaction melting and infiltration involves continuing to heat the temperature at a rate of 3℃ / min to 2050℃ for 2.5 hours.

[0052] Performance testing: The outer layer density of the gradient-modified carbon fiber reinforced ceramic matrix composite was measured to be 2.76 g / cm³. 3 The inner layer density is 2.17 g / cm³. 3 Oxyacetylene ablation tests were conducted according to GJB 323B-2018 standard. The material surface temperature was 2300℃, the test time was 300s, and the measured linear ablation rate was 5.65×10⁻⁶. -4 mm / s; the bending strength at 1600℃ in air was measured to be 240MPa according to GJB 10311-2021 standard.

[0053] Example 3 Example 3 is basically the same as Example 1, except that: In step ②, the deposition temperature is 1050℃, the deposition time is 60h, and the PyC interface layer thickness is 200nm.

[0054] In step ③, the average particle size of ZrC nanoparticles, HfC nanoparticles, TaC nanoparticles, NbC nanoparticles and TiC nanoparticles is 50 nm, and the solid content of the nanocomposite sol is 40 wt%.

[0055] In step ④, the second stage of reaction melting and infiltration involves continuing to heat the temperature at a rate of 4℃ / min to 1750℃ for 1.8h; the third stage of reaction melting and infiltration involves continuing to heat the temperature at a rate of 3℃ / min to 2100℃ for 3h.

[0056] Performance testing: The outer layer density of the gradient-modified carbon fiber reinforced ceramic matrix composite was measured to be 2.79 g / cm³. 3 The inner layer density is 2.12 g / cm³. 3 Oxyacetylene ablation tests were conducted according to GJB 323B-2018 standard. The material surface temperature was 2300℃, the test time was 300s, and the measured linear ablation rate was 5.42×10⁻⁶. -4 mm / s; the bending strength measured in air at 1600℃ according to GJB 10311-2021 standard is 258MPa.

[0057] Example 4 Example 4 is basically the same as Example 1, except that: In step ①, the preform region used to form the outer layer of the carbon fiber reinforced ceramic matrix composite material accounts for 35% of the total thickness of the carbon fiber preform with a gradient porosity structure, the preform region used to form the middle layer of the carbon fiber reinforced ceramic matrix composite material accounts for 45% of the total thickness of the carbon fiber preform with a gradient porosity structure, and the preform region used to form the inner layer of the carbon fiber reinforced ceramic matrix composite material accounts for 20% of the total thickness of the carbon fiber preform with a gradient porosity structure.

[0058] In step ④, the molar ratio of ZrSi2 to Si in the ZrSi2 and Si mixed powder is 2:1; the third stage reaction melting and infiltration is to continue heating at a heating rate of 3℃ / min to 1950℃ for 4 hours.

[0059] Performance testing: The outer layer density of the gradient-modified carbon fiber reinforced ceramic matrix composite was measured to be 2.82 g / cm³. 3 The inner layer density is 2.14 g / cm³. 3 Oxyacetylene ablation tests were conducted according to GJB 323B-2018 standard. The material surface temperature was 2300℃, the test time was 300s, and the measured linear ablation rate was 5.38×10⁻⁶. -4 mm / s; the bending strength measured in air at 1600℃ according to GJB 10311-2021 standard is 232MPa.

[0060] Example 5 Example 5 is basically the same as Example 1, except that: In step ③, the number of cycles of the impregnation-curing-pyrolysis process (i.e., the number of times the impregnation, curing and pyrolysis processes are repeated) is 2.

[0061] In step ④, the first stage of reaction melting and infiltration is to heat to 1480℃ at a heating rate of 6℃ / min for 1.5h; the third stage of reaction melting and infiltration is to continue heating to 1900℃ at a heating rate of 2℃ / min for 4h.

[0062] Performance testing: The outer layer density of the gradient-modified carbon fiber reinforced ceramic matrix composite was measured to be 2.71 g / cm³. 3 The inner layer density is 2.13 g / cm³. 3 Oxyacetylene ablation tests were conducted according to GJB 323B-2018 standard. The material surface temperature was 2300℃, the test time was 300s, and the measured linear ablation rate was 5.94×10⁻⁶. -4 mm / s; the bending strength at 1600℃ in air was measured to be 216MPa according to GJB 10311-2021 standard.

[0063] Comparative Example 1 Comparative Example 1 is basically the same as Example 1, except that: In step ④, instead of using a three-temperature-zone isolated graphite fixture, a single-temperature-zone graphite fixture is used to fill the material thickness direction with high-entropy silicide alloy powder for reactive melting. The high-entropy silicide alloy powder is a mixture of ZrSi2 powder, HfSi2 powder, TaSi2 powder, NbSi2 powder, and TiSi2 powder in a molar ratio of 1:1:1:1:1. The reactive melting is carried out by heating to 2000℃ at a heating rate of 3℃ / min for 3 hours. The reactive melting is carried out under an absolute pressure of 5Pa. After the reactive melting is completed, the furnace is first cooled to 800℃, then purged with argon gas and cooled to 200℃ before being removed from the furnace and then naturally cooled to room temperature in air.

[0064] Performance testing: The overall average density of the carbon fiber reinforced ceramic matrix composite was measured to be 2.88 g / cm³. 3 Oxyacetylene ablation tests were conducted according to GJB323B-2018 standard. The material surface temperature was 2300℃, the test time was 300s, and the measured linear ablation rate was 9.12×10⁻⁶. -4 mm / s; the bending strength at 1600℃ in air was measured to be 185MPa according to GJB 10311-2021 standard.

[0065] Comparative Example 2 Comparative Example 2 is basically the same as Example 1, except that: In step ④, instead of using a three-temperature-zone isolated graphite fixture, a single-temperature-zone graphite fixture is used to fill the entire material thickness direction with pure silicon powder with a particle size of 5μm for reaction melting and infiltration. The reaction melting and infiltration is carried out by heating to 1450℃ at a heating rate of 6℃ / min for 2 hours. After the reaction melting and infiltration is completed, the furnace is first cooled to 800℃, then argon gas is used to cool it to 200℃ before it is taken out of the furnace and then naturally cooled to room temperature in the air.

[0066] Performance testing: The overall average density of the carbon fiber reinforced ceramic matrix composite was measured to be 2.35 g / cm³. 3 Oxyacetylene ablation tests were conducted according to GJB323B-2018 standard. The material surface temperature was 2300℃, the test time was 300s, and the measured linear ablation rate was 17.6×10⁻⁶. -4 mm / s; the bending strength at 1600℃ in air was measured to be 195MPa according to GJB 10311-2021 standard.

[0067] Comparative Example 3 Comparative Example 3 is basically the same as Example 1, except that: In step ④, instead of using a three-temperature zone isolated graphite fixture, a single-temperature zone graphite fixture is used to fill the material thickness direction with a mixture of ZrSi2 and Si powder (the molar ratio of ZrSi2 to Si is 1.5:1) for reaction melting and infiltration. The reaction melting and infiltration is carried out by heating to 1700℃ at a heating rate of 4℃ / min for 1.8h. After the reaction melting and infiltration is completed, the furnace is first cooled to 800℃, then argon gas is used to cool it to 200℃ before it is taken out of the furnace and then naturally cooled to room temperature in the air.

[0068] Performance testing: The overall average density of the carbon fiber reinforced ceramic matrix composite was measured to be 2.85 g / cm³. 3 Oxyacetylene ablation tests were conducted according to GJB323B-2018 standard. The material surface temperature was 2300℃, the test time was 300s, and the measured linear ablation rate was 9.53×10⁻⁶. -4 mm / s; the bending strength at 1600℃ in air was measured to be 190MPa according to GJB 10311-2021 standard.

[0069] Comparative Example 4 Comparative Example 4 is basically the same as Example 1, except that: Step ② is omitted, that is, a carbon fiber preform with a gradient pore structure is directly used to replace the low-density C / C porous preform for subsequent steps.

[0070] Performance testing: Oxyacetylene ablation testing was conducted according to GJB 323B-2018 standard. The material surface temperature was 2300℃, the test time was 300s, and the measured linear ablation rate was 9.08×10⁻⁶. -4mm / s; the bending strength at 1600℃ in air was measured to be 142MPa according to GJB 10311-2021 standard.

[0071] Comparative Example 5 Comparative Example 5 is basically the same as Example 1, except that: In step ③, no hexamethylenetetramine curing agent is added to the nanocomposite sol; it is cured solely by thermosetting phenolic resin. The nanocomposite sol is uniformly mixed from high-entropy carbide ceramic particles, thermosetting phenolic resin (PFJY-5121 type thermosetting phenolic resin with a residual carbon rate of 45%), polyvinyl butyral (PVB), and solvent. The high-entropy carbide ceramic particles are composed of ZrC (zirconium carbide) nanoparticles, HfC (hafnium carbide) nanoparticles, and TaC (tantalum carbide) nanoparticles in a molar ratio of 1:1:1:1:1. The sol is composed of nanoparticles, NbC (niobium carbide) nanoparticles, and TiC (titanium carbide) nanoparticles. The particle size of ZrC nanoparticles, HfC nanoparticles, TaC nanoparticles, NbC nanoparticles, and TiC nanoparticles is 100 nm. The solvent is a mixture of anhydrous ethanol and acetone in a volume ratio of 1:1. The mass ratio of high-entropy carbide ceramic particles to thermosetting phenolic resin is 4:1, and the mass ratio of high-entropy carbide ceramic particles to polyvinyl butyral is 25:1. The solid content of the nanocomposite sol is 35 wt%.

[0072] Performance testing: The outer layer density of the carbon fiber reinforced ceramic matrix composite was measured to be 2.68 g / cm³. 3 The inner layer density is 2.08 g / cm³. 3 Oxyacetylene ablation tests were conducted according to GJB 323B-2018 standard. The material surface temperature was 2300℃, the test time was 300s, and the measured linear ablation rate was 9.89×10⁻⁶. -4 mm / s; the bending strength at 1600℃ in air was measured to be 195MPa according to GJB 10311-2021 standard.

[0073] Comparative Example 6 Comparative Example 6 is basically the same as Example 1, except that: In step ①, T800-12K carbon fiber is used to prepare a carbon fiber preform through a uniform density needle punching process. This carbon fiber preform does not have a gradient pore structure and is used to replace the carbon fiber preform with a gradient pore structure in Example 1 for subsequent steps ② to ⑤. During the uniform density needle punching process, the needle punching density is 30 needles / cm². 2 The interlayer density is 1.0 g / cm³. 3 .

[0074] In step ④, the thickness of the high-temperature zone accounts for 30% of the total thickness of the first composite material, the thickness of the medium-temperature zone accounts for 40% of the total thickness of the first composite material, and the thickness of the low-temperature zone accounts for 30% of the total thickness of the first composite material. Other operations are the same as step ④ in Example 1.

[0075] Performance testing: The outer layer density of the carbon fiber reinforced ceramic matrix composite was measured to be 2.70 g / cm³. 3 The inner layer density is 2.22 g / cm³. 3 Oxyacetylene ablation tests were conducted according to GJB 323B-2018 standard. The material surface temperature was 2300℃, the test time was 300s, and the measured linear ablation rate was 9.24×10⁻⁶. -4 mm / s; the bending strength at 1600℃ in air was measured to be 198MPa according to GJB 10311-2021 standard.

[0076] Comparative Example 7 Comparative Example 7 is basically the same as Example 1, except that: Excluding step ③, a low-density C / C porous preform is directly used to replace the first composite material for subsequent steps.

[0077] Performance testing: The outer layer density of the carbon fiber reinforced ceramic matrix composite was measured to be 2.58 g / cm³. 3 The inner layer density is 2.02 g / cm³. 3 Oxyacetylene ablation tests were conducted according to GJB 323B-2018 standard. The material surface temperature was 2300℃, the test time was 300s, and the measured linear ablation rate was 10.2×10⁻⁶. -4 mm / s; the bending strength at 1600℃ in air was measured to be 188MPa according to GJB 10311-2021 standard.

[0078] Comparative Example 8 Comparative Example 8, referring to Example 1 of CN114380613A, provides an axially gradient planar homogeneous ZrC-SiC modified C / C composite material.

[0079] Performance testing: Oxyacetylene ablation test was conducted according to GJB 323B-2018 standard. The material surface temperature was 2300℃, the test time was 300s, and the measured linear ablation rate was 9.18×10⁻⁶. -4 mm / s; the bending strength measured in air at 1600℃ according to GJB 10311-2021 standard is 212MPa.

[0080] By comparing the examples and comparative examples, it is evident that the gradient-modified carbon fiber reinforced ceramic matrix composite material provided by this invention exhibits excellent performance in terms of high-temperature ablation resistance and high-temperature mechanical properties. Table 1 below shows the performance test results of the materials finally prepared in each example and comparative example.

[0081] Table 1 As shown in Table 1, the gradient-modified carbon fiber reinforced ceramic matrix composites prepared in Examples 1-5, through the synergistic effect of the pore structure gradient constructed by variable density needle punching, the gradient pre-distribution of the high-entropy ceramic precursor, and the ceramic component gradient formed by the three-temperature staged reaction melting and infiltration, exhibit an online ablation rate of 5.38 × 10⁻⁶ at 2300℃ in an oxyacetylene environment. -4 ~5.94×10 -4 The bending strength is not less than 216 MPa in air at 1600℃ and the thickness is mm / s. It also achieves excellent resistance to ultra-high temperature ablation and high-temperature mechanical properties. In Example 4, the outer layer thickness ratio was increased (35%) and the third-stage reaction melting time was extended (4 h), resulting in increased enrichment of the high-entropy ceramic in the outer layer (outer layer density 2.82 g / cm³). 3 The lowest linear ablation rate of 5.38 × 10⁻⁶ was obtained. - 4 mm / s; Example 3, by refining the powder particle size (50nm), increasing the sol solid content (40wt%), and increasing the third-stage melting temperature (2100℃), resulted in a more uniform pre-distribution of high-entropy carbides and a more complete formation of high-entropy solid solution, with a flexural strength reaching up to 258MPa; Example 5 had the fewest impregnation-curing-pyrolysis cycles (2 times) and the lowest third-stage melting temperature (1900℃), with relatively low pre-distribution load and sufficient high-entropy solid solution formation, and all properties were at the lower limit of the examples, indicating that the number of cycles and melting temperature have a significant impact on material properties.

[0082] In contrast, Comparative Examples 1-8 all exhibited significantly deteriorated performance due to the absence of key process steps. Comparative Example 1 employed a single-temperature zone integral filling of high-entropy silicide alloy powder for melting and infiltration. Although high-entropy components were introduced, the lack of gradient design resulted in component segregation along the melting and infiltration path, insufficient formation of the high-entropy solid solution, and stress concentration in the homogeneous high-modulus structure under thermal shock, leading to a linear ablation rate as high as 9.12 × 10⁻⁶. -4 The speed is mm / s, while the overall average density is as high as 2.88 g / cm³. 3 The temperature was significantly higher than in the embodiments, which is not conducive to structural weight reduction; Comparative Example 2 used pure silicon melting and infiltration in a single temperature zone, completely lacking high-entropy ceramic modification, and the SiC matrix underwent active oxidation at 2300℃, with a linear ablation rate as high as 17.6×10 -4mm / s; Comparative Example 3 uses a homogeneous ZrC-SiC matrix formed by the melt infiltration of a mixed powder of ZrSi2 and Si in a single temperature zone, with a linear ablation rate of 9.53 × 10⁻⁶ mm / s; -4 mm / s, which is higher than 9.12 × 10 mm / s in Comparative Example 1. -4 The speed of mm / s indicates that the high-entropy carbide solid solution has better ablation resistance than single ZrC, but is still significantly worse than the gradient distribution examples. In Comparative Example 4, omitting the PyC interface layer resulted in a lack of protection for the carbon fibers during melting and infiltration, weakened interfacial bonding, and a sharp drop in flexural strength to 142 MPa, demonstrating the crucial role of the PyC interface layer in fiber protection and load transfer. In Comparative Example 5, the absence of hexamethylenetetramine curing agent led to insufficient cross-linking of the thermosetting phenolic resin, failure of high-entropy carbide particle anchoring, weakened gradient pre-distribution, and an outer layer density reduced to 2.68 g / cm³. 3 The line ablation rate increased to 9.89 × 10⁻⁶. -4 mm / s. Comparative Example 6 used a homogeneous carbon fiber preform. Due to the lack of a pore structure gradient, the insufficient porosity in the outer layer region led to underperfusion of the high-entropy melt (outer layer density was only 2.70 g / cm³). 3 The excessively high porosity in the inner layer region led to over-percolation of the silicon melt (the inner layer density increased to 2.22 g / cm³). 3 The ceramic component distribution was inaccurate, and the linear ablation rate reached 9.24 × 10⁻⁶. -4 mm / s. Comparative Example 7 omits step ③ and directly uses a low-density C / C porous green body for reaction melting and infiltration. Lacking the high-entropy carbide ceramic particle pre-distribution nucleating agent, the melting and infiltration reaction is insufficient, with an outer layer density of only 2.58 g / cm³. 3 The inner layer density is only 2.02 g / cm³. 3 The line ablation rate reached 10.2×10 -4 mm / s. Comparative Example 8, with its axial gradient ZrC-SiC system, although possessing a structural gradient but lacking high-entropy carbide components, still exhibits a linear ablation rate of 9.18 × 10⁻⁶ mm / s. -4 mm / s indicates that relying solely on structural gradients without high-entropy modification of components is insufficient to meet the ultra-high temperature ablation resistance requirements above 2300℃.

[0083] The above results indicate that only when the pore structure gradient formed by variable density needle punching, the gradient pre-distribution of high-entropy ceramic precursors, and the ceramic component gradient formed by three-temperature staged reaction melting and infiltration work synergistically, and are supplemented by PyC interface layer protection and curing agent crosslinking anchoring, can low linear ablation rate and high temperature and high bending strength be achieved simultaneously in an ultra-high temperature environment of 2300℃. Each process step is indispensable.

[0084] The parts of this invention not described in detail are techniques known to those skilled in the art.

[0085] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A gradient-modified carbon fiber reinforced ceramic matrix composite material, characterized in that: The carbon fiber reinforced ceramic matrix composite material comprises an outer layer, a middle layer, and an inner layer sequentially from the near ablation end to the far ablation end along the thickness direction; The outer layer is a near-ablation surface layer, and the outer layer matrix phase contains (Zr, Hf, Ta, Nb, Ti)C. x High-entropy carbide solid solution and SiC accompanying phase generated in situ during preparation; The intermediate matrix phase is ZrC-SiC; The inner layer is a far-ablation surface layer, and the matrix phase of the inner layer is SiC; The reinforcement of the carbon fiber reinforced ceramic matrix composite material is a carbon fiber preform with a gradient pore structure along the thickness direction.

2. The carbon fiber reinforced ceramic matrix composite material according to claim 1, characterized in that: The thickness of the outer layer accounts for 30-40% of the total thickness of the carbon fiber reinforced ceramic matrix composite material; The thickness of the middle layer accounts for 40-50% of the total thickness of the carbon fiber reinforced ceramic matrix composite material; The thickness of the inner layer accounts for 10-30% of the total thickness of the carbon fiber reinforced ceramic matrix composite material.

3. A method for preparing a gradient-modified carbon fiber reinforced ceramic matrix composite material, characterized in that, The method includes the following steps: (1) A carbon fiber preform with a gradient pore structure was prepared by a variable density needle punching process; (2) A pyrolytic carbon interface layer is deposited on the carbon fiber surface of the carbon fiber preform with a gradient pore structure to obtain a low-density C / C porous preform; (3) Prepare a nanocomposite sol containing five kinds of high-entropy carbide ceramic particles and thermosetting phenolic resin, and use the nanocomposite sol as an impregnation liquid to perform an impregnation-curing-cracking process on the low-density C / C porous preform, so that the high-entropy ceramic precursor is pre-distributed in a gradient along the thickness direction to obtain the first composite material. The high-entropy ceramic precursor is a composite of high-entropy carbide ceramic particles and cracked carbon. (4) The first composite material is placed in a three-temperature zone isolation fixture and subjected to zoned and staged heating reaction melting infiltration to obtain a second composite material including an inner matrix phase, a middle matrix phase and an outer matrix phase; (5) The second composite material is kept at 1600~1800℃ under inert gas protection to obtain a gradient modified carbon fiber reinforced ceramic matrix composite material.

4. The preparation method according to claim 3, characterized in that, In step (1): The carbon fiber preform has a gradient pore structure along the thickness direction; When the carbon fiber preform is prepared using a variable-density needle punching process, the needle punching density in the preform region used to form the outer layer of the carbon fiber reinforced ceramic matrix composite is 45~55 needles / cm². 2 The interlayer density is 0.6~0.8 g / cm³. 3 The porosity is 50-60%, and the needle density of the preform region used to form the middle layer of the carbon fiber reinforced ceramic matrix composite is 25-35 needles / cm. 2 The interlayer density is 0.9~1.1 g / cm³. 3 The porosity is 30-40%, and the needle density of the preform region used to form the inner layer of the carbon fiber reinforced ceramic matrix composite is 15-25 needles / cm. 2 The interlayer density is 1.2~1.4 g / cm³. 3 The porosity is 15-25%.

5. The preparation method according to claim 3, characterized in that, In step (2): The pyrolytic carbon interface layer was deposited by chemical vapor infiltration. The thickness of the pyrolytic carbon interface layer is 200~500 nm; and / or The density of the low-density C / C porous preform is 1.10~1.40 g / cm³. 3 .

6. The preparation method according to claim 3, characterized in that, In step (3): The nanocomposite sol is formed by uniformly mixing high-entropy carbide ceramic particles, thermosetting phenolic resin, hexamethylenetetramine, dispersant and solvent. The high-entropy carbide ceramic particles are composed of ZrC nanoparticles, HfC nanoparticles, TaC nanoparticles, NbC nanoparticles and TiC nanoparticles in a molar ratio of 1:1:1:1:

1. The dispersant is polyvinyl butyral and / or silane coupling agent, and the solvent is anhydrous ethanol and / or acetone. Preferably, the particle size of ZrC nanoparticles, HfC nanoparticles, TaC nanoparticles, NbC nanoparticles and / or TiC nanoparticles is 50~200 nm; Preferably, the residual carbon content of the thermosetting phenolic resin is 40-50%. Preferably, the solvent is a mixture of anhydrous ethanol and acetone in a volume ratio of 1:(0.5~1.5); Preferably, the mass ratio of the high-entropy carbide ceramic particles to the thermosetting phenolic resin is (3~5):1, the mass ratio of the thermosetting phenolic resin to hexamethylenetetramine is (10~15):1, and the mass ratio of the high-entropy carbide ceramic particles to the dispersant is (20~30):

1. Preferably, the solid content of the nanocomposite sol is 30-40 wt%; and / or The impregnation-curing-pyrolysis process is repeated 2 to 4 times. In each impregnation-curing-pyrolysis process, the impregnation is vacuum impregnation, which is carried out under an absolute pressure ≤100Pa. The impregnation time is 30 to 60 minutes. The curing is carried out at 80 to 120℃ for 2 to 4 hours. The pyrolysis is carried out at 900 to 1000℃ for 1 to 3 hours.

7. The preparation method according to claim 3, characterized in that, In step (4): The inner cavity of the three-temperature zone isolation fixture includes, along the thickness direction, a high-temperature zone for filling high-entropy silicide alloy powder, a medium-temperature zone for filling ZrSi2 and Si mixed powder, and a low-temperature zone for filling silicon powder, wherein the high-temperature zone, the medium-temperature zone, and the low-temperature zone are isolated from each other. The high-entropy silicide alloy powder filled in the high-temperature zone is used to form the outer matrix phase of the carbon fiber reinforced ceramic matrix composite material after reaction melting and infiltration. The ZrSi2 and Si mixed powder filled in the medium-temperature zone is used to form the middle matrix phase of the carbon fiber reinforced ceramic matrix composite material after reaction melting and infiltration. The silicon powder filled in the low-temperature zone is used to form the inner matrix phase of the carbon fiber reinforced ceramic matrix composite material after reaction melting and infiltration. The high-entropy silicide alloy powder is composed of ZrSi2 powder, HfSi2 powder, TaSi2 powder, NbSi2 powder and TiSi2 powder mixed in a molar ratio of 1:1:1:1:1; Preferably, in the ZrSi2 and Si mixed powder, the molar ratio of ZrSi2 to Si is (1~2):1; Preferably, the particle size of the high-entropy silicide alloy powder, the ZrSi2 and Si mixed powder, and the silicon powder are all 1~10μm.

8. The preparation method according to claim 3, characterized in that, In step (4), the phased heating reaction infiltration involves placing the first composite material in the three-temperature zone isolation fixture and heating it as a whole, sequentially performing the following three phases of reaction infiltration: The first stage of reaction melting and infiltration involves heating to 1400-1480℃ at a rate of 5-8℃ / min for 1.5-2.5 hours. The second stage of reaction melting and infiltration involves continuing to heat the temperature at a rate of 3~5℃ / min to 1650~1750℃ for 1.5~2 hours. The third stage of reaction melting and infiltration involves continuing to heat the temperature at a rate of 2~4℃ / min to 1900~2100℃ for 2~4 hours. Preferably, all three stages of reaction melting and infiltration are carried out under an absolute pressure ≤10Pa; Preferably, after the third stage of reaction melting and infiltration is completed, the furnace is first cooled to 800°C, and then argon gas is used for further cooling.

9. The preparation method according to claim 3, characterized in that, In step (5): The heat preservation treatment time is 2-4 hours; and / or The carbon fiber reinforced ceramic matrix composite material has a density gradient along its thickness direction, and the density of the outer layer is 2.7~2.82 g / cm³. 3 The density of the inner layer is 2.0~2.3 g / cm³. 3 .

10. A gradient-modified carbon fiber reinforced ceramic matrix composite material prepared by any one of claims 3 to 9.

Citation Information

Patent Citations

  • A type of C f / ZrC-SiC Ultra-High Temperature Ceramic Matrix Composites and Their Preparation Methods

    CN108585906B

  • A gradient ultra-high temperature ceramic matrix composite material and its preparation method

    CN110627517B

  • Preparation method of superhigh-temperature ceramic-based composite material with axial gradient and plane homogeneity

    CN114380613A

  • High-entropy ultrahigh-temperature ceramic-based composite material and preparation method thereof

    CN115385712A